2020
DOI: 10.1101/2020.07.13.20152959
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dissemination and co-circulation of SARS-CoV2 subclades exhibiting enhanced transmission associated with increased mortality in Western Europe and the United States

Abstract: Mechanisms underlying the acute respiratory distress syndrome (ARDS)-like clinical manifestations leading to deaths in patients who develop COVID-19 remain uncharacterized. While multiple factors could influence these clinical outcomes, we explored if differences in transmissibility and pathogenicity of SARS-CoV2 variants could contribute to these terminal clinical consequences of COVID-19. We analyzed 34,412 SARS-CoV2 sequences deposited in the Global Initiative for Sharing All Influenza Data (GISAID) SARS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…Even though there were very limited SARS-CoV-2 complete genome data, many individual studies reported that the virus had gradually accumulated genomic sequence alterations, which were commonly seen in different widely spread viral strains. Particularly, single-nucleotide variants (SNVs) and other types of mutations were found in diverse countries/areas and across multiple time points ( 2 , 3 ) within the 29 903-nucleotide (nt) SARS-CoV-2 complete genome. The SNVs might have potential influence on the viral infectivity, or affect the biological functions, or shape protein structures, such as A23403G causing an AA change on Spike protein: D614G, and mutations on the viral Nsp6 and ORF10 ( 4–6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Even though there were very limited SARS-CoV-2 complete genome data, many individual studies reported that the virus had gradually accumulated genomic sequence alterations, which were commonly seen in different widely spread viral strains. Particularly, single-nucleotide variants (SNVs) and other types of mutations were found in diverse countries/areas and across multiple time points ( 2 , 3 ) within the 29 903-nucleotide (nt) SARS-CoV-2 complete genome. The SNVs might have potential influence on the viral infectivity, or affect the biological functions, or shape protein structures, such as A23403G causing an AA change on Spike protein: D614G, and mutations on the viral Nsp6 and ORF10 ( 4–6 ).…”
Section: Introductionmentioning
confidence: 99%
“…The GH strains were mainly restricted to the USA and partly Eastern Mediterranean (Fig. 1), and mostly spread by cryptic 159 and pre/a-symptomatic transmission 160 . These variants might trade-off virulence by a slower release of virions, and in exchange, benefited from the induction of low immune response in asymptomatic hosts.…”
Section: Resultsmentioning
confidence: 99%
“…After the public awareness and other social interventions, these strains, especially GR have probably increased in fitness. Although Hu and Riley 159 have recently reported the co-circulation of both G and GH strains correlating with mortality in different states, how the association among multiple clades would modulate the evolutionary dynamics is now a burning question. With the new data of GV strains as shown in our study, the previous analysis by Hodcroft et al (2020) 24 can be updated to recent time that may change result of the association.…”
Section: Resultsmentioning
confidence: 99%
“…This limitation in viral confrontation can be attributed to many causes, such as failure to adhere to measures of social distancing, the presence of concomitant chronic diseases strongly correlated to mortality (comorbidities), the preparedness of health systems to cope with the pandemic, and other related factors [3]. Despite the rapid progress of phylogenetic analysis and genetic mapping of SARS-CoV-2, the incidence of concomitant mixed infections with different strains has not been reported [4]. SARS-CoV-2 is similar to SARS-CoV, which resulted in an epidemic in China in 2002.…”
Section: Introductionmentioning
confidence: 99%